PENGARUH METODE BERMAIN PERAN MAKRO TERHADAP PERCAYA DIRI ANAK KELOMPOK B TK NEGERI PEMBINA INDRALAYA - Rizka Supriyanti,; yetty rahelly; hasmalena hasmalena (FKIP Universitas sriwijaya, 2017)
Pre-experimental research with One Shoot Case Study design entitled The Influence of Macro Role Playing Methods On Children Confidence of B group TK Negeri Pembina Indralaya aimed to know the influence of macro role playing on children confidence. To collect the samples of the study, purposive sampling technique in consideration with the low confidence level in B1 class was applied. The sample consisted of 20 children. The treatment was done 4 times with posttest on each treatment. Posttest used an observation aid in form of sheets observation which was showed in form of test scores and was changed to scores consisted of 4 indicators. The scores of each posttest summed by 4 obtained an average score of 78.65. As the data was hypothesized was the data contained in the lower limit class interval BSH score category was 63. The data analysis results obtained t value= 5,19 ? t table value = 1,73 with the significance level 5% and dk= (19). Therefore, it can be concluded that there was an influence of macro role playing on children confidence of B group TK Negeri Pembina Indralaya. It can be seen from each meeting, 3 of 4 indicators occurred dominantly was showing courage when playing a role, showing tolerant attitude when playing role, and showing responsible attitude when playing role, while one less indicator occured that showing the interaction among friends when playing the role. It is expected that in the next lesson, more trained interaction indicators among friends when playing role.